Who's in for success? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Farming Solutions Website, recently launched by Greenpeace, Oxfam, Pesticide Action Network Africa and the Information Centre on Low Energy Input Agriculture is by nature a success story. It presents successful initiatives and projects which...